Urban Mediascapes and Multicultural Flows: Assessing Vancouver’s Communication Infrastructure - Ahadi, Daniel (Canadian Journal of Communication, 2009)
This paper adopts a communication infrastructure model in mapping the flow and meaning of ethnic media in Vancouver and their interaction with local, national, and global conceptions of a public commons. A communication infrastructure consists of a “thick” social network of media and organizations, which create and disseminate everyday conversations and news to any given community. Without the existence of a sustainable communication infrastructure, communities cannot form and function. The intersection of social capacity and media infrastructure, then, becomes an important predictor of potential for democratic deliberation and political engagement. Presenting an empirical study of ethnic media in Vancouver, this article asks how well these outlets provide resources to construct inclusion in an urban setting. A more complex infrastructure was mapped than anticipated, but several blind spots were still found. A set of recommendations is made to expand the politics of inclusion and recognition of shared citizenship and civic engagement.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjIyMzAvY2pjLjIwMDl2MzRuNGEyMTIy